The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s11524-012-9670-1
|View full text |Cite|
|
Sign up to set email alerts
|

Estimates of the Population Prevalence of Injection Drug Users among Hispanic Residents of Large US Metropolitan Areas

Abstract: Little information exists on the population prevalence or geographic distribution of injection drug users (IDUs) who are Hispanic in the USA. Here, we present yearly estimates of IDU population prevalence among Hispanic residents of the 96 most populated US metropolitan statistical areas (MSAs) for 1992-2002. First, yearly estimates of the proportion of IDUs who were Hispanic in each MSA were created by combining data on (1) IDUs receiving drug treatment services in Substance Abuse and Mental Health Services A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…To unfold, enculturation requires a cultural enclave. There is a sizeable Puerto Rican PWID population in the Northeast (CDC, 2010; Pouget et al, 2012), and in NYC, the presence of Spanish-monolingual immigrant Puerto Rican PWID is documented (Gelpí-Acosta et al, 2011; Neaigus et al, 2013). A qualitative study found a risk-prone “Puerto Rican-way of injecting drugs” that endorses syringe sharing among “brothers,” (immigrant-only) perpetuating their injection risks in NYC (Gelpí-Acosta et al, 2011).…”
Section: 4 Discussionmentioning
confidence: 99%
“…To unfold, enculturation requires a cultural enclave. There is a sizeable Puerto Rican PWID population in the Northeast (CDC, 2010; Pouget et al, 2012), and in NYC, the presence of Spanish-monolingual immigrant Puerto Rican PWID is documented (Gelpí-Acosta et al, 2011; Neaigus et al, 2013). A qualitative study found a risk-prone “Puerto Rican-way of injecting drugs” that endorses syringe sharing among “brothers,” (immigrant-only) perpetuating their injection risks in NYC (Gelpí-Acosta et al, 2011).…”
Section: 4 Discussionmentioning
confidence: 99%
“…PWID prevalence for non-Hispanic white adults remained relatively flat over time (median values ranged between 86 and 97 injectors per 10,000 adults). Hispanic PWID prevalence rate also declined significantly (1992 mean = 192, median = 133; 2002 mean = 144, median = 93) [45].…”
Section: Introductionmentioning
confidence: 93%
“…[See these selected papers that describe trends in PWID or in HIV among PWID (Chatterjee et al, 2011; Cooper et al, 2008; Pouget, Friedman, Cleland, Tempalski, & Cooper, 2012; Tempalski et al, 2009, 2013; West et al, 2016); in services for PWID (Tempalski, Cleland, Chatterjee, Pouget, & Friedman, 2010); and predictors of service presence or coverage (Friedman et al, 2007; Tempalski et al, 2003, 2007, 2008). ] Instead, we briefly and selectively summarize some key findings from five of these papers that directly addressed the predictors of PWID population prevalence or HIV prevalence or incidence at the metropolitan level, and then discuss some implications of these findings.…”
mentioning
confidence: 99%